Magnetic Fullerenes inside Single-Wall Carbon Nanotubes - Simon, F.; Kuzmany, H.; Náfrádi, B.; Fehér, T.; Forró, L.; Fülöp, F.; Jánossy, A.; Korecz, L.; Rockenbauer, A.; Hauke, F.; Hirsch, A. (Physical review letters, 2006)
C(59)N magnetic fullerenes were formed inside single-wall carbon nanotubes by vacuum annealing functionalized C(59)N molecules encapsulated inside the tubes. A hindered, anisotropic rotation of C(59)N was deduced from the temperature dependence of the electron spin resonance spectra near room temperature. Shortening of the spin-lattice relaxation time T(1) of C(59)N indicates a reversible charge transfer toward the host nanotubes above approximately 350 K. Bound C(59)N-C(60) heterodimers are formed at lower temperatures when C(60) is coencapsulated with the functionalized C(59)N. In the 10-300 K range, T(1) of the heterodimer shows a relaxation dominated by the conduction electrons on the nanotubes.